You can retire while you're still young enough to enjoy it - Ambromovitz, Les (Dearborn ChicagoUS, 1999)
Explains how to plan financially for early retirement by saving, investing and tapping miscellaneous sources of income. Provides parenting strategies for raising financially responsible children; and discusses retirement options such as: part-time employment, and opening a small business. Discourages involvement in work-at-home schemes.